2018
DOI: 10.1097/iae.0000000000001848
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Obstructive Sleep Apnea and the Presence and Severity of Diabetic Retinopathy

Abstract: The findings suggest an increased risk of DR, proliferative DR, and diabetic macular edema in patients with severe OSA. Ophthalmologists following these patients should be aware of this association to better manage ocular sequelae of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 35 publications
0
32
1
Order By: Relevance
“…Longitudinal data have also shown that OSA is a risk factor for DR progression and that treatment with continuous positive airway pressure reduced this risk [6]. Other studies have also found that more severe OSA is associated with DME [27]. While we did show that moderate OSA and AHI were associated with moderate DR and VTDR, we did not find any significant associations between mod OSA or AHI and DME.…”
Section: Discussioncontrasting
confidence: 74%
“…Longitudinal data have also shown that OSA is a risk factor for DR progression and that treatment with continuous positive airway pressure reduced this risk [6]. Other studies have also found that more severe OSA is associated with DME [27]. While we did show that moderate OSA and AHI were associated with moderate DR and VTDR, we did not find any significant associations between mod OSA or AHI and DME.…”
Section: Discussioncontrasting
confidence: 74%
“…Oxygen desaturation was significantly inversely related to microalbuminuria, microvascular complications, retinopathy, and HbA1c. In another study, Change et al retrospectively evaluated 317 people with DR and OSA, with review of polysomnography, coding and medical records [68]. After adjustment, an association was seen between DR and severe OSA (OR: 2.18, 95% confidence CI: 1.14-4.18, P = 0.019).…”
Section: Diabetic Retinopathy (Dr)mentioning
confidence: 99%
“…More recently, Leong et al performed a systematic review and meta-analysis of the effect of OSA on DR and maculopathy [72]. In the systematic review, they included 16 studies: one longitudinal, the rest cross-sectional, and all the studies listed above were included, except for the two which were published later [68,70]. Three studies were included in the meta-analysis.…”
Section: Diabetic Retinopathy (Dr)mentioning
confidence: 99%
“…Obstructive Sleep Apnoea (OSA) is characterized by the episodic collapse of the upper airway during sleep resulting in repeated apnoeic episodes with concomitant increases in arterial blood pressure and reductions in blood oxygen saturation levels. [13][14][15] More broadly, OSA has been implicated as a risk factor in other ophthalmic conditions including glaucoma, nonarteritic anterior ischemic optic neuropathy, central serous chorioretinopathy and floppy eyelid syndrome. 8 Several comorbidities, including an increased prevalence of hypertension, obesity and cardiovascular disease are common within the OSA population.…”
Section: Introductionmentioning
confidence: 99%
“…12 Recent studies have explored potential relationships between OSA and other retinal disease, specifically diabetic retinopathy where OSA has been reported as an independent risk factor in the progression of diabetic retinopathy. [13][14][15] More broadly, OSA has been implicated as a risk factor in other ophthalmic conditions including glaucoma, nonarteritic anterior ischemic optic neuropathy, central serous chorioretinopathy and floppy eyelid syndrome. 16 Although the exact pathogenesis of MacTel remains unclear, it has been postulated that Müller cell dysfunction may play a critical role throughout the disease process.…”
Section: Introductionmentioning
confidence: 99%